Feasibility study of focal lens for multistatic microwave breast imaging - Godinho, Daniela M. (2022)
Microwave Imaging is an emerging technique to aid breast cancer diagnosis. Current multistatic setups involve complex and heavy signal processing techniques, such as to remove the energy coupling between adjacent sensors, which masks the response from inner tissues. We investigate a novel approach using a dielectric lens in order to reduce the coupling effects between antennas, thus reducing the signal processing burden, while preserving all the advantages of multistatic setups. In this paper, we show that we can successfully detect simulated breast targets on reconstructed images using a setup with a dielectric lens.